PENGARUH STRUKTUR MODAL, PROFITABILITAS, DAN LEVERAGE TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2019-2021 - Rufaidah Laela; Bachtiar Rahman Halik (Jurnal Ekonomi dan Bisnis, 2023)
This research aims to determine and conduct an analysis of the influence of capital structure, profitability and leverage on company value. The technique used in this research for sampling is a purposive sampling technique. By collecting data,. 66 companies were used in the research sample with a total population of 34 food and beverage sector companies that were registered on the IDX. Data analysis in this research was carried out using statistical data processing using SPSS version 25 tools. Based on the results of data analysis using the t test (SPSS V25), it can be seen that partially Capital Structure has no influence on Company Value, Profitability has a significant effect on Company Value and leverage has no influence on Company Value. Meanwhile, based on the results of data analysis using the F test (SPSS V25), it can be seen that simultaneously or concurrently, Capital Structure, Profitability and Leverage have a significant effect on Company Value.